2020
DOI: 10.1002/pros.24054
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal and pelvic adipose tissue distribution and risk of prostate cancer recurrence after radiation therapy

Abstract: Background Fat distribution varies between individuals of similar body mass index (BMI). We hypothesized that visceral obesity is more strongly associated with poor prostate cancer outcomes than overall obesity defined by BMI. Materials and Methods We quantified abdominal visceral and subcutaneous fat area (VFA and SFA), and pelvic periprostatic adipose tissue area (PPAT), using computed tomography scans from radiation‐treated prostate cancer patients at the Durham North Carolina Veterans Administration Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…Sarcopenia has become a topic of great interest in oncology [68]; however, poorly understood given the lack of reporting on assessment characteristics and definitions. For example, although studies had reported the time of body composition assessment [25,33,34,36,37,[40][41][42][43]45], the high heterogeneity and lack of standardisation could misclassify prostate cancer patients with obesity or sarcopenia and, therefore, mask the impact of these outcomes on overall survival. Future research should better inform definitions (i.e., cut-off values and rationale) and time of assessments, and information about clinical factors associated with muscle mass accrual or maintenance in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sarcopenia has become a topic of great interest in oncology [68]; however, poorly understood given the lack of reporting on assessment characteristics and definitions. For example, although studies had reported the time of body composition assessment [25,33,34,36,37,[40][41][42][43]45], the high heterogeneity and lack of standardisation could misclassify prostate cancer patients with obesity or sarcopenia and, therefore, mask the impact of these outcomes on overall survival. Future research should better inform definitions (i.e., cut-off values and rationale) and time of assessments, and information about clinical factors associated with muscle mass accrual or maintenance in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Supplementary eAppendix 2). A total of 16 cohort studies undertaking retrospective analyses [16,24,25,[33][34][35][36][37][38][39][40][41][42][43][44][45] were included in the primary analysis. During the eligibility assessment, six additional studies [46][47][48][49][50][51] were initially selected and authors contacted given the lack of specific information on the results for prostate cancer patients.…”
Section: Studies Included and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…On an organism scale, obesity is found to promote tumorigenesis through elevated levels of adipokines, growth factors, steroid hormones, chronic inflammation producing reactive oxygen species (ROS), and a change in gut microbiota [84]. For example, it has been proven that accumulated visceral fat, which is a hallmark of obesity, correlates with primary tumor recurrence, poor prognosis, and chemotherapeutic resistance [85,86] In that setting, adipose tissue plays a significant role by excreting adipokines, with LCN2 being one of them. Some authors even suggest that LCN2 expressed by adipose tissue causes the activation of both MMP-2 and MMP-9, which are promoters of tumorigenesis, and they found especially increased circulating concentrations of the LCN2/MMP-9 complex, which is known for its tissue remodeling properties [87].…”
Section: Lcn2 and Its Significance In Hepatocellular Carcinomamentioning
confidence: 99%